An eating pattern characterised by skipped or delayed breakfast is associated with mood disorders among an Australian adult cohort - J. E. Wilson; L. Blizzard; S. L. Gall; C. G. Magnussen; W. H. Oddy; T. Dwyer; K. Sanderson; A. J. Venn and K. J. Smith (Cambridge University Press, 2022)
Background
Meal timing may influence food choices, neurobiology and psychological states. Our exploratory study examined if time-of-day eating patterns were associated with mood disorders among adults.
Methods
During 2004–2006 (age 26–36 years) and 2009–2011 (follow-up, age 31–41 years), N = 1304 participants reported 24-h food and beverage intake. Time-of-day eating patterns were derived by principal components analysis. At follow-up, the Composite International Diagnostic Interview measured lifetime mood disorder. Log binomial and adjacent categories log-link regression were used to examine bidirectional associations between eating patterns and mood disorder. Covariates included sex, age, marital status, social support, education, work schedule, body mass index and smoking.
Results
Three patterns were derived at each time-point: Grazing (intake spread across the day), Traditional (highest intakes reflected breakfast, lunch and dinner), and Late (skipped/delayed breakfast with higher evening intakes). Compared to those in the lowest third of the respective pattern at baseline and follow-up, during the 5-year follow-up, those in the highest third of the Late pattern at both time-points had a higher prevalence of mood disorder [prevalence ratio (PR) = 2.04; 95% confidence interval (CI) 1.20–3.48], and those in the highest third of the Traditional pattern at both time-points had a lower prevalence of first onset mood disorder (PR = 0.31; 95% CI 0.11–0.87). Participants who experienced a mood disorder during follow-up had a 1.07 higher relative risk of being in a higher Late pattern score category at follow-up than those without mood disorder (95% CI 1.00–1.14).
Conclusions
Non-traditional eating patterns, particularly skipped or delayed breakfast, may be associated with mood disorders.